Nomenclatural problems among Thysanoptera (Insecta) of Costa Rica - Goldarazena, Arturo; A. Mound, Laurence; zur Strassen, Richard (Revista de Biología Tropical, 2008)
We present data to argue that several recent papers on the Thysanoptera of Costa Rica are affected by unsatisfactory technical procedures, including failure to recognize intraspecific structural variation. Fourteen new synonyms are recognized for Costa Rica Thysanoptera, nine generic and five specific.